2013
DOI: 10.1007/s00125-013-2850-z
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis at the onset of type 1 diabetes is associated with future HbA1c levels

Abstract: Aims/hypothesis We investigated the long-term impact of diabetic ketoacidosis (DKA) at onset on metabolic regulation and residual beta cell function in a Danish population with type 1 diabetes. Methods The study is based on data from DanDiabKids, a Danish national diabetes register for children. The register provides clinical and biochemical data on patients with type 1 diabetes diagnosed in 1996-2009 and then followed-up until 1 January 2012. Repeated-measurement models were used as statistical methods.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
75
5
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 34 publications
12
75
5
5
Order By: Relevance
“…It is known that younger age at diagnosis of DKA is associated with lower HbA1c but higher glucose concentrations2122. We too found a similar observation with the cohort from Kuwait.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It is known that younger age at diagnosis of DKA is associated with lower HbA1c but higher glucose concentrations2122. We too found a similar observation with the cohort from Kuwait.…”
Section: Resultssupporting
confidence: 88%
“…In our study, the frequency of severe DKA (8.8%) is comparable and significantly lower than in Spain (17.8%)27 or France (14.8%)28, but was much higher than that reported from Denmark (1.7%)29.…”
Section: Discussioncontrasting
confidence: 58%
“…In mainland Italy, DKA frequency at time of diabetes diagnosis (41.9%) was consistent with recent reports from other countries, such as France (43.9%)14 and Brazil (42.3%)15, and with a recent Italian study based on two years of observation (38.5%)7. The DKA frequency in Italian children at diagnosis of type 1 diabetes was somewhat higher than that reported in Austria (34.0%)5, Germany (21.1%)3, New Zealand (25.0%)16 and the U.S. (31.1%)17 and, disappointingly, close to twice that reported in Finland (22.4%)18 and Denmark (17.9%)19 and in Canada (18.6%)20. However, it should be noted that there were minor differences in the definition of DKA used in the studies.…”
Section: Discussionmentioning
confidence: 67%
“…We have demonstrated that metabolic control has improved7 and severe hypoglycemic events have decreased 8,9. Furthermore, diabetic ketoacidosis at disease onset is associated with worse metabolic control and higher daily insulin requirement for equal HbA1c values (ie, higher insulin dose-adjusted [IDA]A1c)10 several years after diagnosis 11…”
Section: Examples Of Researchmentioning
confidence: 99%